Visualizing ideas : from scribbles to storyboards. - Krisztian, Gregor, ....-; Schlempp-Ülker, Nesrin, ....- (London : Thames and Hudson, 2006)
Visualize and present your ideas quickly and effectively with the aid of this superbly illustrated book. Gregor Krisztian and Nesrin Schlempp-Ulker explore and explain basic layout techniques, giving expert tips, and demonstrating useful tricks employed by professionals. It is an indispensable reference work for all professional designers and students - indeed, for anyone who wishes to present their ideas successfully and skilfully.
Keywords: Tekenen